Observer-Based Adaptive Fuzzy Output Feedback Control of Fractional-Order Chaotic Systems With Input Quantization - Qiu, Hongling; Huang, Chengdai; Tian, Huanhuan; Liu, Heng (Frontiers in Physics, 2022)
This paper studies the adaptive fuzzy output feedback control problem for strict-feedback fractional order chaotic systems with unmeasurable states and input quantization. Firstly, the functional uncertainties are approximated by fuzzy logic systems (FLSs). Secondly, combining the FLS and the system output signal, an observer is constructed to estimate the unmeasurable states. A command filter is employed to deal with the ``explosion of complexity'' problem resulted from repeated derivatives of virtual control inputs in each backstepping step. To compensate for quantization errors, a hyperbolic tangent function is introduced to transform the control signal, which can not only guarantee that the tracking error converges to an arbitrarily small region near the origin, and all the signals of the closed-loop system are bounded based on the fractional Lyapunov stability criterion, but also reduce the chattering phenomenon of the control input. Finally, a numerical simulation example is put forward to verify the effectiveness of our method.